Estrategia de publicidad y promoción para el mejoramiento del posicionamiento del Centro Turístico Balneario Ecológico Piscis de la parroquia San Luis de Pambil, cantón Guaranda, Año 2023 - Yanchaliquin Azogue, Alexandra Maribel (2024)
In the contemporary world, the tourism sector is highly competitive and dynamic, where visibility and effective promotion are crucial to attract travelers. However, many tourist destinations often go under the radar due to a lack of strong marketing strategies. The Pisces Ecological Spa Tourist Center, located in the San Luis de Pambil Parish, Guaranda Canton, faces a lack of recognition and visibility despite its natural charms and attractions. This thesis addresses the challenge of improving your positioning through effective advertising and promotion strategies. The main purpose of this thesis is to address the lack of recognition and visibility of the Centro Turístico Balneario Ecológico Piscis and propose a comprehensive advertising and promotion strategy that not only increases its recognition at a local and national level, but also contributes to the economic development of the local community. The research is based on a situational analysis of the resort, a comprehensive review of the literature related to advertising, promotion and positioning in the tourism sector, and the formulation of specific strategies supported by data and market analysis. This study reveals the critical need to improve the recognition and visibility of the Pisces Ecological Spa Resort. The implementation of the proposed strategies has the potential to transform the tourist center into an attractive destination and contribute to the economic and tourist growth of the San Luis de Pambil Parish. Keywords: Advertising, promotion, positioning, strategies, tourist center, San Luis de Pambil Parish.